Discovery of 2 n gametes in tetraploid oat Avena vaviloviana - Katsiotis, Andreas; Forsberg, R. A. (My University, 1995)
Sexual polyploidization via the action of 2 n gametes (gametes with the sporophytic chromosome number) has been identified as the most important evolutionary mode of polyploidization among plant genera. This study was conducted to determine whether 2 n gametes are present in the tetraploid level of the genus Avena (2 n=4×=28) Twenty tetraploid Avena lines, representing four species and one interspecific hybrid, were screened for pollen grain size in order to differentiate between n and 2 n pollen. Avena vaviloviana (Malz.) Mordv. line PI 412767 was observed to contain large pollen grains at a 1.0% frequency. Cytogenetic analyses of pollen mother cells of PI 412767 revealed cells with double the normal chromosome number (i.e., 56 chromosomes at metaphase I and anaphase I). The mode of chromosome doubling was found to be failure of cell wall formation during the last mitotic division that preceded meiosis. The resulting binucleate cells underwent normal meiotic divisions and formed pollen grains with 28 chromosomes. Based on the formation and function of 2 n gametes, three models involving diploid and tetraploid oat lines are proposed to describe possible evolutionary pathways for hexaploid oats. If stable synthetic hexaploid oat lines could be developed by utilizing 2 n gametes from diploid and tetraploid oat species through bilateral sexual polyploidization, the resulting hexaploids could be used in breeding programs for transferring genes from diploids and tetraploids to cultivated hexaploids. © 1995 Kluwer Academic Publishers.
Keywords: 2 n gametes; Avena; binucleate cell; evolution; sexual polyploidization